PENGARUH LEVERAGE DAN PENDAPATAN SAHAM TERHADAP NILAI PERUSAHAAN DENGAN MANAJEMEN LABA SEBAGAI VARIABEL INTERVENING PADA PERUSAHAAN PERBANKAN YANG TERDAFTAR DI BEI - K, Putri Lailatul; Meyrsa Rosanti, Shenia; Tyas, Hesti Ning; W, Amalia Devi; Pranoto, Felix Chandra; Suparta, I Made (Jurnal Valuasi: Jurnal Ilmiah Ilmu Manajemen dan Kewirausahaan, 2025)
This study discusses the effect of leverage and stock income on company value with profit management as an intervening variable in banking companies listed on the IDX for the 2023 period. This research was conducted by using secondary data.  Secondary data in this study is in the form of annual financial statements of banking companies listed on the IDX in 2023 and this research data is obtained through the Indonesia Stock Exchange website. This study uses the Partial Least Square (PLS) data analysis method. According to Jogiyanto and Abdillah (2015), PLS is a variant-based structural equation analysis (SEM) that can simultaneously test measurement models (testing validity and reliability) as well as structural testing for causality tests (testing hypotheses with prediction models). The purpose of this study is to find out whether there is an influence of leverage and stock income on the value of banking companies on the IDX